2009
DOI: 10.1590/s0100-06832009000300018
|View full text |Cite
|
Sign up to set email alerts
|

Correction of soil acidity in the subsurface of an oxisol with sandy loam texture under no-tillage

Abstract: In Rio Grande do Sul State (RS), Southern Brazil, aluminum saturation in many areas under no-till system is high and base saturation low in the 0.10-0.20 m layer (subsurface), which may reduce the grain yield of annual crops. The objective of this study was to evaluate if the occurrence of high aluminum saturation and low base saturation in the subsurface, under a no-till system, represents a restrictive environment for crop production, as well as to evaluate forms of lime incorporation for soil acidity correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
(19 reference statements)
0
2
0
7
Order By: Relevance
“…Ausências de diferenças na produtividade das culturas em razão da calagem na superfície ou com incorporação de calcário em SPD foram encontradas em diferentes situações: recém-implantado (Oliveira e Pavan, 1996), em área há quatro anos em SPD (Rossato et al, 2009); por 12 anos, com reaplicações de calcário, incorporadas ou na superfície do solo, a cada quatro anos (Marcolan e Anghinoni, 2006); e após seis e 10 e 11 a 13 anos (Wortmann et al, 2010) da intervenção mecânica.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Ausências de diferenças na produtividade das culturas em razão da calagem na superfície ou com incorporação de calcário em SPD foram encontradas em diferentes situações: recém-implantado (Oliveira e Pavan, 1996), em área há quatro anos em SPD (Rossato et al, 2009); por 12 anos, com reaplicações de calcário, incorporadas ou na superfície do solo, a cada quatro anos (Marcolan e Anghinoni, 2006); e após seis e 10 e 11 a 13 anos (Wortmann et al, 2010) da intervenção mecânica.…”
Section: Resultsunclassified
“…Ausências de diferenças de produtividades das culturas em SPD foram constatadas seja pela intervenção mecânica (Stavi et al, 2011) ou pela incorporação de calcário ao solo (Oliveira e Pavan, 1986;Marcolan e Anghinoni, 2006;Quincke et al, 2007;Rossato et al, 2009;Wortmann et al, 2010).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Tal sentimento é justificável, já que a calagem não tem um efeito rápido na redução da acidez do subsolo pois depende da lixiviação de sais por meio do perfil do solo (CAIRES et al, 2003). No entanto, na Região Sul do país, Rossato et al (2009) verificaram que a aplicação de calcário em superfície em áreas estabelecidas há quatro anos com o SPD em um Latossolo Vermelho distrófico de textura franco arenosa, apesar de ser menos eficiente na correção da acidez do subsolo, não apresentou diferença na produtividade de soja, milho e trigo em comparação com tratamentos em que o calcário foi incorporado na camada arável. Esse resultado corrobora com os de Fidalski et al (2015) que também não encontraram vantagens da incorporação do calcário em relação à aplicação de SPD em superfície do solo, em um Latossolo Vermelho Distroférrico de textura muito argilosa, há 17 anos.…”
Section: Principais Problemas Em Relação Ao Manejo Do Solounclassified
“…Studies on soil amendment in areas under the no-tillage system for grain production have shown that the effect of liming applied on the surface for amendment of subsoil layers varies with the application rate and particle size of the product, the form of application, the type of soil, the climatic conditions (especially water regime), the growing system, and the period of time since application ALLEONI et al, 2005;CRUSCIOL, 2008a;ROSSATO et al 2009), which leads to controversy regarding the effectiveness of this practice, particularly for acidity amendment of the subsoil.…”
Section: Introductionmentioning
confidence: 99%